An introduction to mass and heat transfer - Middleman, Stanley (New York : John Wiley and Sons, 1998)
This book provides more than sufficient material to support a one-semester course in mass and heat transfer; curricula that need to present mass and heat transfer separately in two one-quarter segments are served abundantly.
Keywords: Heat; Transmission; Mass transfer; Heat -- Transmission; Mass transfer